Weighting Surprise Parties: Some Problems for Schroeder. Issue 1 (31st July 2015) - RISBERG, OLLE
Abstract : In this article I argue against Schroeder's account of the weight of normative reasons. It is shown that in certain cases an agent may have reasons she cannot know about without them ceasing to be reasons, and also reasons she cannot know about at all. Both possibilities are troubling for Schroeder's view.